Currency convertibility, monetary management and the development of capital markets : some paradigms from Southern Africa - Clarke, Laurence ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Surveys the capital market scene in Southern Africa and the Caribbean. Examines the issue of currency convertibility and how it relates it to the two regions under survey. Examines also currency convertibility and some implications for monetary management in both regions.